A DIVISÃO SEXUAL DO TRABALHO NA INDÚSTRIA TÊXTIL: INTERLOCUÇÕES COM A ERGONOMIA / The sexual division of work in the textile industry: interlocutions with ergonomics (Trabalho & Educação, 2018)
The present research is inserted in "Line II: Formative Processes in Technological Education " of the Graduate Program in Technological Education of CEFET-MG, which focuses on work-education issues in socioeconomic and political-cultural contexts, highlighting historical processes and cultural relations between societal changes, education and the world of work. In this context, it seeks to unveil the interplay between the sexual division of labor and ergonomics in the textile industry, and from there it demonstrates the importance of the sex / gender variable in studies on work and ergonomics. In order to do so, we used the theoretical constructions of the Sociology of French Labor, present in the concept of the sexual division of labor as the material basis of the social relations of sex / gender, as well as in the Ergonomics approaches. The field research was carried out in a textile company located in the metropolitan Region of Belo Horizonte, State of Minas Gerais. All the quantitative and qualitative data were collected and analyzed from the documents made available by the company, the on-site observations and semi-structured interviews with the managers of the operational areas. The research was categorized into three aspects: (i) the sexual division of labor in the textile industry; (ii) the relationship between productive work and reproductive work in the domestic sphere; and (iii) Ergonomics. The articulation of these categories of analysis made possible the approximation of the object of study: the interlocution between the sexual division of labor and ergonomics in the textile industrial sector. The analysis of the results reveals a marked segregation by gender in the company with a larger contingent of women in the spinning, auxiliary and operator positions, while the men stand out in the processing / finishing and maintenance sector, as well as in the positions of leadership and command. It was found that in the conception of the company and workers there is work of man and work of woman, that require different aptitudes. Women are required for tasks / functions that are considered "light" and require manual skills, such as dexterity and perfection in the execution of details or to operate machines, in a simple and repetitive work. Patience, docility, and discipline are also considered positive elements of female workforce. The preference for male workers for other tasks / functions is justified by arguments in which the need for physical strength often appears. However, even in the spinning sector, mostly female, the men are the ones who hold the most qualified positions and functions and are in charge of the tasks that demands, besides physical strength, technical knowledge and command. Women are more accepted in tasks that require greater care and attention, especially cleaning activities and compliance checking in detail. The results pointed to a silencing of gender relations in the textile industrial sector, especially when analyzing the ergonomic conditions of the activities in the perspective of a sexual and active subjectivity, which makes this interlocution difficult.___A presente pesquisa se insere na “Linha II: Processos Formativos em Educação Tecnológica” do Programa de Pós-Graduação em Educação Tecnológica do CEFET-MG, que focaliza questões da área trabalho-educação nos contextos socioeconômico e político-cultural, destacando os processos históricos e culturais, as relações entre as mudanças societárias, a educação e o mundo do trabalho. Nesse contexto, busca desvelar a interlocução entre a divisão sexual do trabalho e a ergonomia na indústria têxtil, e, a partir daí demonstra a importância da variável sexo/gênero nos estudos sobre o trabalho e a ergonomia. Para realiza-la recorreu-se às construções teóricas da Sociologia do Trabalho Francesa, presentes no conceito da divisão sexual do trabalho como base material das relações sociais de sexo/gênero, bem como nas abordagens da ergonomia. A pesquisa de campo foi realizada em uma empresa do ramo de têxtil situada na Região metropolitana de Belo Horizonte, Estado de Minas Gerais. Todos os dados quantitativos e qualitativos foram coletados nos documentos disponibilizados pela empresa, nas observações in loco e em entrevistas semiestruturadas com os gestores e as trabalhadoras das áreas operacionais. Os dados foram analisados em três aspectos: (i) divisão sexual do trabalho na indústria têxtil; (ii) a relação entre trabalho produtivo e trabalho reprodutivo no âmbito doméstico; e (iii) ergonomia. A articulação dessas categorias de análise tornou possível a aproximação do objeto de estudo: a interlocução existente entre a divisão sexual do trabalho e a ergonomia no setor industrial têxtil. A análise dos resultados revela uma marcada segregação por gênero na empresa com um contingente maior de mulheres no setor de fiação e nos cargos de auxiliar e operadora, enquanto os homens destacam-se no setor de beneficiamento/acabamento e manutenção, assim como nos cargos de chefia e comando. Constatou-se que na concepção da empresa e das próprias trabalhadoras existe trabalho de homem e trabalho de mulher, que requerem aptidões diferenciadas. As mulheres são requisitadas para tarefas/funções consideradas “leves” e que demandam habilidades manuais, como destreza e perfeição na execução de detalhes ou para operar máquinas, num trabalho simples e repetitivo. A paciência, a docilidade e a disciplina também são competências consideradas positivas da força de trabalho feminina. A preferência por trabalhadores homens para outras tarefas/funções é justificada com argumentos nos quais aparecem frequentemente a necessidade de força física. No entanto, mesmo no setor de fiação, majoritariamente feminino, são os homens que ocupam os cargos/funções mais qualificados e estão nas tarefas que requerem, além de força física, conhecimento técnico e comando. As mulheres são mais aceitas nas tarefas que exigem maior cuidado e atenção, principalmente atividades de limpeza e verificação de conformidade em detalhes. Os resultados apontaram para um silenciamento das relações sociais de sexo/gênero no setor industrial têxtil, sobretudo quando se analisam as condições ergonômicas das atividades na perspectiva de uma classe trabalhadora sexuada, o que dificulta essa interlocução.